An Analysis of the Application of Indonesian Spelling Conventions in President Joko Widodo’s 2024 State Speech - Ade Almadun; Dedek Darvina; Shaqilla Putri Perdana; Eva Dwi Kurniawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The state speech is the highest form of formal government communication in conveying information and policy direction to the public. Therefore, the use of Indonesian in this document must adhere to standard rules according to the Indonesian Spelling Guidelines (EYD V 2023). This study aims to identify spelling errors and provide recommendations for improvements in President Joko Widodo's 2024 State Speech. The research method used a qualitative descriptive approach with document analysis techniques. Data, in the form of speech texts published by ANTARA News, were then analyzed based on spelling error categories, including punctuation, capitalization, writing numbers and currency, loan terms/foreign words, diction/word choice, and sentence structure. The results showed 11 cases of spelling inconsistencies in the speech manuscript, spread across various sections of the text. The most dominant errors related to the use of capital letters and the writing of loan words that did not conform to KBBI rules. These findings indicate the need for a more rigorous editing process and the implementation of a language audit before the official speech manuscript is published. In this way, the quality of language in state communication can be improved so that it continues to reflect the identity and authority of the national language.